Jakarta Post Capital: A study on human resources readiness in the transition towards a global city - Pratama, Ferdianta Wahyu Nur; Rahman, Syahrir (Jurnal Kependudukan Indonesia, 2025)
Following the 2023-2026 regional development plan, which outlines the relocation of the capital to Nusantara, Jakarta is poised to become the epicentre of global economic growth by transforming it into a global city by 2045. The relocation of the capital, accompanied by the transfer of civil servants to Kalimantan, will result in a shift in the demographic structure of Jakarta. This paper aims to examine Jakarta's projected population following the relocation of the capital up to 2045 and to study the profile and preparedness of the human capital in Jakarta to support the development of a global city, with a particular focus on the education sector. This study employs a cohort component approach to project the population of Jakarta until 2045. The results demonstrate that, across all three scenarios, the city's population will decline. However, the proportion of the population in the productive age group remains significant, at approximately 70%. Nevertheless, the dependency ratio remains high, exceeding 40% in all observed years. This situation presents a substantial challenge for Jakarta in its endeavour to become a global city, particularly given the current state of human resources, which requires an improvement in its quality of education.